Through the doors of the wardrobe: A qualitative case study of a short-term study abroad program inspired by the C.S. Lewis Trail in Ireland - Keely Cline; Elizabeth Dimmitt; Victoria Seeger (Irish Journal of Academic Practice, 2022)
This qualitative case study explores experiences of U.S. American undergraduate students who participated in a short-term study abroad program to the Republic of Ireland and Northern Ireland. The program focused on psychological perspectives of childhood and play including restorative benefits of spending time in nature. Additional features of the program included using a children’s novel to connect class content and travels as well as prioritizing outdoor experiences. Students shared reflections on their experiences through digital storytelling projects and interviews. Analysis of data resulted in identification of five themes and researcher assertions. The study is framed in relation to literature contrasting short-term and long-term study abroad and the use of reflective practices including digital storytelling in study abroad.